Aeronautics New Advances - Anwar Ali, Zain; Cvetković, Dragan (IntechOpen, 2022)
This book provides a comprehensive overview of aeronautics. It discusses both small and large aircraft and their control strategies, path planning, formation, guidance, and navigation. It also examines applications of drones and other modern aircraft for inspection, exploration, and optimal pathfinding in uncharted territory. The book includes six sections on agriculture surveillance and obstacle avoidance systems using unmanned aerial vehicles (UAVs), motion planning of UAV swarms, assemblage and control of drones, aircraft flight control for military purposes, the modeling and simulation of aircraft, and the environmental application of UAVs and the prevention of accidents.